New and noteworthy records of Orthoptera (Insecta) from Crete (Greece) and its satellite islets - Nefeli Kotitsa; Dragan Chobanov; Apostolos Trichas; Moisis Mylonas (Travaux du Muséum National d’Histoire Naturelle “Grigore Antipa”, 2025)
Crete (Greece) and its satellite islets have been identified as a significant biodiversity hotspot with a high concentration of endemic species, including Orthoptera. So far, 76 species of Orthoptera have been recorded from Crete and its surrounding islets, 21 of which are endemic to the area. The present study contributes to the understanding of the Orthopteran fauna of Crete and its satellite islets by presenting new records and findings derived from 37 years of pitfall-trap samplings by the Natural History Museum of Crete (NHMC). Seven species are added to the species list for Crete and its satellite islets (Pteronemobius heydenii, Stenonemobius gracilis, Paramogoplistes novaki, Paramogoplistes kinzelbachi, Rhacocleis andikithirensis, Rhacocleis graeca, Rhacocleis insularis), while new records and distribution data are provided for five Cretan endemic taxa (Dolichopoda paraskevi, Ovaliptila lindbergi, Troglophilus spinulosus, Platycleis albopunctata cretica, Rhacocleis derrai). New species records and checklists are provided for four satellite islets of Crete (Gavdos, Gavdopoula, Dia, Chrysi). As a result, the number of taxa known from this island group is increased to 83, 21 of which are endemic to Crete and Gavdos and eight are endemic to the South Aegean.